Co-clustering of EphB6 and ephrinB1 in trans restrains cancer cell invasion - Lung-Yu Liang; Niall D. Geoghegan; Michael Mlodzianoski; Andrew Leis; Lachlan W. Whitehead; Minglyanna G. Surudoi; Samuel N. Young; Peter Janes; Doulin Shepherd; Debnath Ghosal; Kelly L. Rogers; James M. Murphy; et al. (Communications Biology, 2024)
Abstract EphB6 is an understudied ephrin receptor tyrosine pseudokinase that is downregulated in multiple types of metastatic cancers. Unlike its kinase-active counterparts which autophosphorylate and transmit signals upon intercellular interaction, little is known about how EphB6 functions in the absence of intrinsic kinase activity. Here, we unveil a molecular mechanism of cell-cell interaction driven by EphB6. We identify ephrinB1 as a cognate ligand of EphB6 and show that in trans interaction of EphB6 with ephrinB1 on neighboring cells leads to the formation of large co-clusters at the plasma membrane. These co-clusters exhibit a decreased propensity towards endocytosis, suggesting a unique characteristic for this type of cell-cell interaction. Using lattice light-sheet microscopy, 3D structured illumination microscopy and cryo-electron tomography techniques, we show that co-clustering of EphB6 and ephrinB1 promotes the formation of double-membrane tubular structures between cells. Importantly, we also demonstrate that these intercellular structures stabilize cell–cell adhesion, leading to a reduction in the invasive behavior of cancer cells. Our findings rationalize a role for EphB6 pseudokinase as a tumor suppressor when interacting with its ligands in trans.